2003
DOI: 10.1046/j.1365-2672.2003.01993.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of visible faecal material as a vehicle for generic Escherichia coli, coliform, and other enterobacteria contaminating poultry carcasses during slaughtering

Abstract: Aims: A comparison of Enterobacteriaceae, coliform and Escherichia coli counts in chicken carcasses with and without visible faecal contamination was conducted to evaluate the role of contamination as a vehicle for generic E. coli, coliform and other enterobacteria contaminating broiler chicken carcasses when processed under routine commercial operations. Methods and Results: Samples were removed from the processing line immediately after evisceration, insideoutside shower and chilling for microbiological anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 8 publications
1
22
0
5
Order By: Relevance
“…Recorded counts after evisceration of chicken (C2) varied among slaughterhouses, without a coherent pattern (Table 3), while the microbiological counts in the chicken carcasses after pre-chilling (C3) were higher in Sl2 when compared to Sl1 and Sl3 for all researched microbiological groups (p<0.0.5, Table 3). The higher temperatures in the chilling tanks from Sl2 when compared to Sl1 and Sl3 can explain these results (Table 5), showing that temperature and water renewal were more important as factors of microbiological control than chlorine, which on its own showed no effect, as also observed by Allen et al (2000), Jimenez et al (2003), Matias et al (2010), and Rodrigues et al (2008). Chilling is considered to play a major role in microbiological contamination during chicken slaughtering, and studies assessing the use of alternative procedures and equipment, such as spraying of cold air instead of immersion in cold water, indicate its relevance in reducing the counts in chicken carcasses (Hutchison et al, 2006;Vaidya et al, 2005;Zweifel et al, 2015).…”
Section: Methodsmentioning
confidence: 59%
“…Recorded counts after evisceration of chicken (C2) varied among slaughterhouses, without a coherent pattern (Table 3), while the microbiological counts in the chicken carcasses after pre-chilling (C3) were higher in Sl2 when compared to Sl1 and Sl3 for all researched microbiological groups (p<0.0.5, Table 3). The higher temperatures in the chilling tanks from Sl2 when compared to Sl1 and Sl3 can explain these results (Table 5), showing that temperature and water renewal were more important as factors of microbiological control than chlorine, which on its own showed no effect, as also observed by Allen et al (2000), Jimenez et al (2003), Matias et al (2010), and Rodrigues et al (2008). Chilling is considered to play a major role in microbiological contamination during chicken slaughtering, and studies assessing the use of alternative procedures and equipment, such as spraying of cold air instead of immersion in cold water, indicate its relevance in reducing the counts in chicken carcasses (Hutchison et al, 2006;Vaidya et al, 2005;Zweifel et al, 2015).…”
Section: Methodsmentioning
confidence: 59%
“…In addition, studies have also revealed that strains of E. coli can be isolated within 40 feet radius outside the poultry house (Davis and Morishita, 2005). Thus, indicating that the reason why the pathogen is considered as a major contaminant in poultry processing plant ( Jimenez et al, 2003).The findings further provides substantial evidence as to the reason why E. coli is the most predominantly isolated bacteria obtained from the liver samples. Furthermore, the presence of the isolated pathogens can also be due to carcass contamination or the presence of ongoing infection prior to slaughter.…”
mentioning
confidence: 72%
“…Jimenez et al (2003) reported that 11.3% of carcasses showed faecal material and 5.2% showed bile on the surface after the evisceration step. The absence of Escherichia coli over the entire period of storage or of other coliform microflora at the beginning of storage is indicative of a good hygienic profile of samples (Zeitoun et al 1994).…”
Section: Discussionmentioning
confidence: 99%